Analytical pyrolysis handbook - Sam, Karen D.; Wampler, Thomas P., 1948- (Boca Raton : CRC Press, 2021)
"Provides a comprehensive view of analytical pyrolysis, beginning with theory and instrumentation, and a vast view of current applications. Provides readers with an essential, one-stop guide for determining if pyrolysis meets application-specific needs, performing pyrolysis, and handling data"--
Revised edition of: Applied pyrolysis handbook / edited by Thomas P. Wampler. 2nd ed. c2007.
OCLC-licensed vendor bibliographic record.
Keywords: Pyrolysis -- Handbooks, manuals, etc; SCIENCE / Chemistry / Analytic; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Material Science